Maintenance Guide for Florida Microirrigation Systems - Thomas Obreza (EDIS)
Florida’s microirrigation systems are technically more complex than sprinkler or flood irrigation systems. They require significant maintenance to assure maximum operational efficiency. The intent of this guide is to help Florida microirrigation system managers and operators keep their systems running at top efficiency, which will improve crop production and conserve Florida’s water resources. This document is CIR 1449, a circular of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2004.